#TITLE_ALTERNATIVE# - MIRZA (NIM 15105062), AFIF
This final project discusses empirical equations from direct comparison between echo intensities and field samples of suspended sediment concentration. Empirical equation is used to convert echo intensities into suspended sediment concentration with field samples of suspended sediment for calibration. Data were obtained from three measurement sites situated in the North of West Java, which are Semak Daun Island, Gembong river mouth, and Indramayu. Measurements were done with Doppler type hydro-acoustic instruments AWAC (600kHz frequency) and Aquadopp (600kHz and 1000kHz frequencies). Water samplings were also conducted in the three measurement sites to obtain suspended sediment concentration. Empirical equations are evaluated by comparing samples of suspended concentrations with estimated suspended sediments concentration. The results show that the estimated concentration depends on frequency instrument and measurement location. Sensitivity from 1000kHz frequency instrument is higher than 600kHz instrument. Accuracy assessment is considered from comparison between estimated dan measured concentration and classified into a factor of two (comparison value is between 0,5 and 2). The result shows that factor of two fitness level have value more than 60% in Semak Daun island and Gembong river mouth, while in Indramayu, it is still below 60%. It should be noted that the result of estimation by using empirical equations in this study is relative, because it did not consider the calibrations of instrument characteristics and sediment properties. Eventhough, it is expected that the results of this study is enough to give an insight of Doppler type hydro-acoustic instruments application for estimating suspended sediment concentration.